Concentration and Size Effects in Electrophysical Properties of Thin Films Based on Permalloy and Silver - Pazukha, I. M.; Shuliarenko, D. O.; Pylypenko , O. V.; Оvrutskyi M. S.; Odnodvorets , L. V. (Physics and Chemistry of Solid State, 2020)
Complex study of electrophysical properties (the electrical resistivity r and the temperature coefficient of resistance (TCR) b) of thin-film samples based on ferromagnetic alloy Ni80Fe20 (permalloy) and noble metal Ag in a wide composition range and within the range of thickness 20-100 nm done. Thin films were obtained by the method of electron-beam co-evaporation technique at room temperature. Their composition was investigated using the method of X-ray spectrometry. The phase state was analyzed by the electron diffraction method. It was demonstrated that the crystal structure of thin films stays unchanged during the annealing process to 500 K. The size and concentration dependences of r and b values were obtained. The corresponding maximum and minimum at the concentration of Ag atoms of 50-60 at.% observed at the dependences r(cAg) and b(cAg). Size dependences r(d) and b(d) associated with the size effects in thin-film materials.